Psychological Burden and Associated Factors of the COVID-19 Pandemic on People in Quarantine and Isolation Centers in Ethiopia: A Cross-Sectional Study - Misgana, Tadesse; Tesfaye, Dejene; Tariku, Mandaras; Ali, Tilahun; Alemu, Daniel; Dessie, Yadeta (Frontiers in Psychiatry, 2022)
Background: Globally, a lot of countries put into practice early quarantine measures as an essential COVID-19 prevention mechanism. Other than physical effects, quarantine has a major result on mental health and well-being at both the individual as well as the community level at large. Therefore, this study aimed to assess the psychological burden of COVID-19 on the people in quarantine and isolation centers and to identify associated factors for early and effective psychosocial intervention during the pandemic and beyond. Method: A cross-sectional study was done among 392 suspected cases of COVID-19 that were in quarantine and isolation centers found in Eastern Ethiopia in 2020. Participants were selected by the convenience sampling method. The common mental disorder was measured by the Self Reporting Questionnaire-20 (SRQ-20). Logistic regression was done to identify predictive factors, and a P < 0.05 was considered statistically significant. Results: The common mental disorder among suspected cases of COVID-19 in Ethiopia was found to be 13.5% (95% CI: 10.2, 17.1%). Female (AOR = 1.52, 95% CI: 1.1, 2.92), known chronic medical illness (AOR = 7.0, 95% CI: 2.2, 21.8), inadequate accessibility of personal protective equipment (AOR = 6.1, 95% CI: 2.8, 13.3), poor awareness about the pandemic (AOR = 2.90, 95% CI: 2.71, 7.54), presence of symptoms of the disease (AOR = 5.3, 95% CI: 2.57, 11.1), and substance use (AOR = 2.7, 95% CI: 1.2, 6.1) were found to be associated with a common mental disorder. Conclusion: The current study revealed that the common mental disorder was relatively high among suspected cases of COVID-19 in quarantine and isolation centers as compared with the general population. The results of the present study demonstrate that some subpopulations are more vulnerable to the pandemic's deleterious effects on mental health. Therefore, providing appropriate psychosocial intervention for the populations at risk is important to decrease the effect of common mental disorders among suspected cases of COVID-19.